The Effect of Adolescent Therapeutic Group Therapy (TKT) on the Development of Adolescent of Islamic Boarding School in Tasikmalaya - Kustiawan, Ridwan; Somantri, Iwan (Jurnal Berita Ilmu Keperawatan, 2022)
The stage of adolescent development is a unique stage of development, adolescents must face changes both physically, cognitively, and emotionally that can cause stress and trigger a unique behavior in adolescents. Today's Muslim youth are many who follow the Islamic boarding school program. This causes the development of adolescents that are less than optimal, if they cannot adapt to the life of the Islamic boarding school, so that it can interfere with the learning process in the Islamic boarding school. And furthermore, their mental health will be disturbed in their adolescent development, such as being less independent, unable to make decisions and having difficulty interacting with peers. One of the efforts to deal with developmental problems faced by adolescents is the therapeutic group therapy (TKT) approach. The purpose of this study was to determine the effect of therapeutic group therapy on the ability of adolescents to stimulate identity development in high school students at the Ibadurrahman Islamic Boarding School, Tasikmalaya City. The design used is "Quasi experimental pre and post- test without control group". The population in this study were all students at the Ibadurrahman Islamic Boarding School, Tasikmalaya City, amounting to 374 respondents with a sample size of 80 students. Analysis using paired-t test (T-test paired). Respondents were divided into 6 groups, with each group totaling 13-14 students. The implementation of TKT for each group is carried out every week with a time of 60 minutes. The results showed a significance value of = 0.001 , there is a significant difference in the average ability to stimulate identity development scores between before and after TKT treatment. This TKT can be done as a therapy to improve adolescent development.